Efficacy of hydrophilic or lipophilic emulsions containing Echinacea purpurea extract in treatment of different types of pruritus - Kilic A; Harder A; Reich H; Knie U; Masur C; Abels C (Dove Medical Press, 2018)
Ana Kilic, Anastasia Harder, Hubert Reich, Ulrich Knie, Clarissa Masur, Christoph Abels Dr. August Wolff GmbH & Co. KG Arzneimittel, Bielefeld, Germany Background: Pruritus reduces quality of life and may occur at different sites of the body. To alleviate pruritus, lipid replenishing and rehydration of the skin is often unsatisfactory. Thus, products with additional antipruritic effects are needed. Objectives: Antipruritic effects and cosmetic properties of two different emulsions, water-in-oil (w/o) or oil-in-water (o/w), and a shampoo containing a lipophilic Echinacea purpurea root extract (Ec.-extract) were assessed in adults suffering from pruritus. Methods: Adults (n = 55) with pruritus of the body applied a w/o emulsion for 2 weeks. In a separate study, adults (n = 33) with a pruritic scalp applied an o/w-emulsion for 4 weeks. In a third study, shampoo (n = 34) was applied for 4 weeks. Objective (erythema, dryness, and papules) and subjective (intensity, duration, and burden of pruritus) parameters were assessed. Results: Treatment with the w/o emulsion significantly reduced erythema and dryness (P < 0.0001) as well as pruritus (in 93% of participants) on the body. Treatment with the o/w-emulsion on the scalp significantly (P < 0.0001) reduced objective (erythema in 61% and dryness in 85% of participants) and subjective (85% of participants had reduced pruritus) parameters. Similar results in reduction of dryness (76% of participants) and pruritus (70 % of participants) were seen after 4 weeks of shampoo use. Conclusion: Independent from the type of emulsion (w/o or o/w), cosmetic products containing a proprietary Ec.-extract significantly reduced objective and subjective parameters in adults suffering from acute or chronic pruritus exhibiting excellent tolerability. Keywords: acute pruritus, chronic pruritus, water-in-oil emulsion, oil-in-water emulsion, lipophilic Echinacea purpurea root extract